A Nature-Based Solution for Coastal Protection: Wind Tunnel Investigations on the Influence of Sand-Trapping Fences on Sediment Accretion - Eichmanns, Christiane; Schüttrumpf, Holger (Frontiers in Built Environment, 2022)
Sand trapping fences are a frequently used nature-based solution in coastal protection for initiating and facilitating coastal dune toe growth. However, only a few researchers have evaluated the trap efficiency of sand trapping fences based on their porosity and height. Subsequently, the design of their properties has only been based on empirical knowledge, to date. However, for restoring and maintaining coastal beach-dune systems, exact knowledge of sand trapping fence's optimal properties is essential. Thus, we conducted physical model tests focussing on the most crucial parameters: fence height (h = 40, 80, 120 mm) and fence porosity (ε = 22.6, 41.6, 56.5%). These tests occurred in an indoor subsonic, blowing-sand wind tunnel equipped with a moveable sediment bed (d50 ~ 212 µm). The experimental mean wind velocities were u1 = 6.1 m/s, u2 = 7.4 m/s, and u3 = 9.3 m/s. We used a hot-wire anemometer to measure the flow fields, a vertical mesh sand trap to determine the sediment fluxes, and a 2D laser scanner to record the sediment accretion around the sand trapping fences over time. The study results provide substantial theoretical and practical support for the installation and configuration of trapping fences and improving their design. The fence porosity, for example, should be chosen depending on the installation purpose. While denser fence porosities (ε1 = 22.6% and ε2 = 41.6%) can be used for initiating and facilitating the dune toe growth, fences with higher porosity (ε3 = 56.5%) are more suitable to favor the sediment accretion between foredunes and white dunes as they allow further dune growth downwind.